STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KRAKTER RELIGIUS DI SMA NEGERI 1 SINGOSARI - Sheilla Mauliya Riswanda; Abdul Jalil; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Lack of attention and interest in Islamic religious education in students towards religious character. Therefore, the formation of a bad religious character into a good religious character must be carried out regularly and directed, as is the case with the various programs in SMA Negeri 1 Singosari. With this background, this research has a research focus, namely to find out what programs are in knowing what programs can shape the religious character of students. By using a qualitative approach and using the type of case study research, namely the data collected in the form of pictures, written or spoken words from the people observed, this research is not in the form of numbers and not statistical data. From the results of observations and interviews that researchers have conducted, researchers found the results of several programs that can shape religious character, namely: dhuha prayer and dhuhur prayer in congregation, prayer before starting and ending lessons, istighosah together, and commemoration of Islamic holidays. With this program, the character of students will be formed even better.